Dynamic response improvement of a bidirectional interleaved buck-boost converter - Lei, Yihan (Nanyang Technological University, 2024)
The robust and fast dynamic response is an essential requirement for the bidirectional interleaved buck-boost converters (IBBs), especially during load disturbance conditions or operation mode switching (from charging mode to discharging mode, or from constant current charging mode to constant voltage charging mode, etc.). This project aims to develop the simulation model of a 20 kW two-phase IBB converter to realize different dynamic response improvement methods, e.g., the voltage single close loop control, the voltage and current double closed-loop control, and the model predictive control. The developed simulation model and control algorithms will also be validated on a 20 kW two-phase IBB laboratory prototype.